The Cambridge companion to British Black and Asian literature (1945-2010) - Osborne, Deirdre,Ed (Cambridge companions to literature)
"This Companion offers a comprehensive account of the influence of contemporary British Black and Asian writing in British culture. While there are a number of anthologies covering Black and Asian literature, there is no volume that comparatively addresses fiction, poetry, plays and performance, and provides critical accounts of the qualities and impact within one book. It charts the distinctive Black and Asian voices within the body of British writing and examines the creative and cultural impact that African, Caribbean and South Asian writers have had on British literature. It analyzes literary works from a broad range of genres, while also covering performance writing and non-fiction. It offers pertinent historical context throughout, and new critical perspectives on such key themes as multiculturalism and evolving cultural identities in contemporary British literature. This Companion explores race, politics, gender, sexuality, identity, amongst other key literary themes in Black and Asian British literature. It will serve as a key resource for scholars, graduates, teachers and students alike"--